2013
DOI: 10.1371/journal.pone.0077185
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Sex, Stroke and Distance on the Lactate Characteristics in High Performance Swimming

Abstract: BackgroundIn order to achieve world-class performances, regular performance diagnostics is required as an essential prerequisite for guiding high performance sport. In high performance swimming, the lactate performance diagnostic is an important instrument in testing the sport specific endurance capacity. Although the role of lactate as a signaling molecule, fuel and a gluconeogenic substrate is accepted, lactate parameters are discussed concerning stability, explanatory power and interpretability.MethodsWe ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 44 publications
(105 reference statements)
2
17
0
3
Order By: Relevance
“…The change in pH during an "Ice Mile" has an almost perfect inverse correlation with the change in lactate, indicating that lactate accumulation is the main reason in causing metabolic acidosis. Lactate plays a role as a signaling molecule, fuel, and a gluconeogenic substrate (14). In addition, the change in pH also correlated very largely with the increase in cortisol level, indicating that the intense exercise causes a considerable metabolic stress.…”
Section: Discussionmentioning
confidence: 98%
“…The change in pH during an "Ice Mile" has an almost perfect inverse correlation with the change in lactate, indicating that lactate accumulation is the main reason in causing metabolic acidosis. Lactate plays a role as a signaling molecule, fuel, and a gluconeogenic substrate (14). In addition, the change in pH also correlated very largely with the increase in cortisol level, indicating that the intense exercise causes a considerable metabolic stress.…”
Section: Discussionmentioning
confidence: 98%
“…The blood lactate significantly increased with the gradually enhanced achievement (LI, 2010). Conversely, Halfslder et al reported that the mean blood lactate concentration decreased in longer distance of swimming (Holfelder et al, 2013). In another study conducted by Sawka et al (Sawka et al, 1979), swimmers in the 200-yd butterfly, back, breast and freestyle races had similar mean blood lactate concentrations (ranging from 16.4-20.6 mm/l).…”
Section: Introductionmentioning
confidence: 92%
“…Gender is controversially associated with different aerobic fitness and blood lactate levels, and performance in swimming [11,21], thus it is plausible to observe differences in the protocol application for male and female athletes. Even though female athletes were evaluated in prior studies evaluating aerobic swimming force [26,28], differences to male athletes are not explored.…”
Section: Polynomial Goodness Of Fit Constancy Level Of Intensity Andmentioning
confidence: 99%